3D surface measurement of static and dynamic objects in underwater environments based on the propagation and projection of CW sinusoidal signal at 532 nm. (January 2022) - Chen, Bingquan; Li, Hongsheng; Wang, Ruirong; Shi, Peng
Abstract: This work carries out both theoretical and experimental studies on three dimensional surface measurement of objects in underwater environments based on the use of the projection of continuous-wave laser-beam-based monochromatic structured light. The mathematical analysis and description of the generation and propagation of sinusoidal fringe patterns in air and underwater environments are presented, which provides the physical basis for the proposed method of measuring the underwater objects. In the experimental investigation we completed the in-door measurements of both static and dynamic objects located in a tank filled with real turbid seawater or lake water. Experimental results have indicated that the proposed approach is capable of yielding high-accuracy reconstructions for underwater 3D imaging of both static and dynamic objects, which shows the possibility of building a portable instrument based on the optical design and measuring technique presented in this work for carrying out high-accuracy in-situ underwater measurement. Highlights: Generation of sinusoidal fringe pattern featured with coherence and monochromaticity. Propagation of coherent structured light in scattering and absorbing media. High-accuracy reconstruction for underwater 3D-shape measurement. In-situ measurement and reconstruction for both static and dynamic objects.